Cellular and molecular complementary immune stress markers for the model species Dreissena polymorpha. Issue 107 (December 2020) - Le Guernic, Antoine; Geffard, Alain; Rioult, Damien; Bigot-Clivot, Aurélie; Leprêtre, Maxime; Palos Ladeiro, Mélissa
Abstract: This study aimed to combine cellular and molecular analyses for better detail the effects of various stresses on a sentinel species of freshwater invertebrate. For this purpose, the hemocytes of the zebra mussel, Dreissena polymorpha, were exposed to different stresses at two different intensities, high or low: chemical (cadmium and ionomycin), physical (ultraviolet B), or biological ones ( Cryptosporidium parvum and Toxoplasma gondii ). After exposure, flow cytometry and droplet digital PCR analyses were performed on the same pools of hemocytes. Several responses related to necrosis, apoptosis, phagocytosis, production of nitric oxide and expression level of several genes related to the antioxidant, detoxification and immune systems were evaluated. Results showed that hemocyte integrity was compromised by both chemical and physical stress, and cellular markers of phagocytosis reacted to ionomycin and protozoa. While cadmium induced oxidative stress and necrosis, ionomycin tends to modulate the immune response of hemocytes. Although both biological stresses led to a similar immune response, C. parvum oocysts induced more effects than T. gondii, notably through the expression of effector caspases gene and an increase in hemocyte necrosis. This suggests different management of the two protozoa by the cell. This work provides new knowledge of biomarkers in the zebra mussel, at both cellular and molecular levels, and contributes to elucidate the mechanisms of action of different kinds of stress in this species. Highlights: Characterization of cellular and molecular markers on zebra mussel hemocytes. Ex vivo exposure to different stresses (chemical, physical and biological). Cellular integrity and functions were impaired by all stresses. Highlighting of different responses to stress at the two levels of living organization.